Seismic performance of non-ductile RC frames with brick infill - Shing, P. Benson; Stavridis, Andreas N.; Koutromanos, Ioannis A.; Willam, Kaspar; Blackard, Ben; Kyriakides, Marios; Billington, Sarah L.; Arnold, Scott (My University, 2009)
This paper summarizes some of the findings of a research project that investigates the seismic performance of masonry-infilled, non-ductile, RC frames, including the development of reliable analytical methods for performance assessment and effective retrofit techniques. Quasi-static tests were conducted on small and large-scale, single-story, single-bay, RC frames infilled with brick masonry walls with and without openings. Some of the infill walls were strengthened with an engineered cementitious composite material. Furthermore, two 2/3-scale, three-story, two-bay, masonry-infilled, RC frames were tested on a shake table. One was tested with no retrofit measures, and the other had infill walls strengthened with the engineered cementitious composite and fiber reinforced polymeric material in the first and second stories, respectively. The tests have demonstrated the effectiveness of the retrofit measures. Computation models that combine smeared and discrete cracks have been developed and validated by the experimental data. Some of the experimental and numerical results are presented in this paper. © 2009 ASCE.
Keywords: Reinforced concrete; Masonry materials; Infilled frame